Isolation of Bacillus sphaericus from Lombok Island, Indonesia, and Their Toxicity against Anopheles aconitus - Bambang Fajar Suryadi; Bagyo Yanuwiadi; Tri Ardyati; Suharjono (International Journal of Microbiology)
Malaria is endemic to Lombok Island, Indonesia. One approach to suppress malaria spread is to eliminate anopheline larvae in their habitat and the environmentally safe agent is bacteria, that is, Bacillus sphaericus. However, there is no information regarding local isolate of B. sphaericus that is toxic to mosquito larvae from Lombok. The aims of the study were to isolate B. sphaericus from soil in areas close to beach surrounding Lombok Island and to test their toxicity against 3rd instar Anopheles aconitus larvae. Soil samples were collected from 20 different sampling locations from Lombok Island and homogenized with sterile physiological salt solution. Suspension was heat-shocked at 80°C for 30 minutes and then spread onto antibiotic-supplemented NYSM solid medium. Colonies grown were characterized and subjected to initial toxicity test against anopheline larvae. Isolates with more than 50% killing percentage were subjected to bioassay testing against anopheline larvae. From 20 locations, 1 isolate showed mild toxicity (namely, isolate MNT) and 2 isolates showed high toxicity (namely, isolates SLG and TJL2) against An. aconitus. Those 3 isolates were potentially useful isolates, as they killed almost all larvae in 24 hours. The discovery of toxic indigenous isolates of B. sphaericus from Lombok Island opens opportunity to develop a biopesticide from local resources.